2017
DOI: 10.3389/fnhum.2017.00180
|View full text |Cite
|
Sign up to set email alerts
|

Increased Gamma Connectivity in the Human Prefrontal Cortex during the Bereitschaftspotential

Abstract: The Bereitschaftspotential (BP) is a slow negative cortical potential preceding voluntary movement. Since movement preparation is dependent upon the synchronous activity of a variety of neurons, BP may develop through the exchange of information among motor-related neurons. However, the relationship between BP and information flow is not yet well-known. In the present study, we aimed to investigate how the connectivity in the prefrontal cortex (PFC) changes during the occurrence of BP. Electrocorticography (EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
(40 reference statements)
1
12
0
Order By: Relevance
“…Information exchange gradually increased prior to the movement onset, peaked during movement, and decreased after movement offset for both intra-connectivity of 1M and inter-connectivity of DLPFC-1M. The findings imply that the connectivity between DLPFC and 1M may also reflect the planning of movement, such as RP[ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Information exchange gradually increased prior to the movement onset, peaked during movement, and decreased after movement offset for both intra-connectivity of 1M and inter-connectivity of DLPFC-1M. The findings imply that the connectivity between DLPFC and 1M may also reflect the planning of movement, such as RP[ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, besides involvement of the cortico-basal ganglia-thalamo-cortical loop (motor loop), a number of studies indicate that the prefrontal cortex (PFC), a region that was found to be tightly linked to the concept of willpower 12 (i.e. the capacity to control one’s own thoughts and actions, as well as the ability to override an unwanted thought, feeling or impulse), decision making and executive control 13 , plays a critical role for initiation of voluntary movements 14 . Particularly the medial part of the PFC (mPFC) was shown to be important for regulating neuronal circuits linked to fear and anxiety 15 .…”
Section: Introductionmentioning
confidence: 99%
“…These two slopes are characterized with reference to the baseline electroencephalography (EEG) activity as BP1 and BP2 [4]. These components of the MRCP have been studied across many different populations [5]- [7], notably in the context of motor training [8]- [12]. One motivation to use EEG data is to provide a low cost and simple method to quantify motor training compared to other approaches such as functional magnetic resonance imaging, magnetoencephalography, and transcranial magnetic stimulation [13].…”
Section: Introductionmentioning
confidence: 99%